Clean and Healthy Living Behavior of Traders in Oeba Market - Yolenta Mariani; Petrus Romeo; Enjelita M Ndoen (Universitas Nusa Cendana, 2021)
Clean and Healthy Living Behavior (PHBS) is an effective way of preventing disease transmission risks in markets. However, the poor implementation of PHBS remains in the traditional markets of Kupang City. This study was to describe the PHBS of traders in Oeba Market, Kupang City. The PHBS includes the behavior of disposing of garbage, using healthy latrines, and throwing saliva. This study is qualitative research with seven informants consisting of one market unit head, five traders, and one cleaning service. Data were collected using in-depth interviews and observations around the market environment. The research findings showed that of the three PHBS indicators studied, informants have only sufficiently implemented the utilization of healthy latrines. The lack of facilities and support from stakeholders has exacerbated the implementation of PHBS by traders in the Oeba market. Providing enabling and reinforcing factors is necessary for the PHBS implementation by Oeba Market traders